Garbhagriha of Lakshmana Temple in Khajuraho - Temples of India Project Team (Jio Institute, 2024)
Entrance to the Garbhagriha, Lakshmana Temple, Khajuraho, Madhya Pradesh, India. Chandella period, reign of Yasovarman, 954 CE. Image courtesy: Arunima Tiwari.